2018
DOI: 10.1111/jocs.13717
|View full text |Cite
|
Sign up to set email alerts
|

Type A interrupted aortic arch and type III aortopulmonary window with anomalous origin of the right pulmonary artery from the aorta

Abstract: Interruption of the aortic arch, aortopulmonary window, and anomalous origin of the right pulmonary artery from the ascending aorta are very rare congenital anomalies. It is even rarer to have all three anomalies in the same setting. We present a case of a newborn who was diagnosed with these lesions and describe the primary repair of these anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Complications mainly presented as great vessel narrowing and residual defects. Most patients (58.6%) suffered from RPA stenosis as a result of either compression by the aorta or excessive tension on the pulmonary anastomosis [53]. In the reports we reviewed, 44.8% and 3.4% of the patients had stenosis at the aortic arch and residual APW, respectively, which accords with the findings of a previous study [6].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Complications mainly presented as great vessel narrowing and residual defects. Most patients (58.6%) suffered from RPA stenosis as a result of either compression by the aorta or excessive tension on the pulmonary anastomosis [53]. In the reports we reviewed, 44.8% and 3.4% of the patients had stenosis at the aortic arch and residual APW, respectively, which accords with the findings of a previous study [6].…”
Section: Discussionsupporting
confidence: 88%
“…A closed ductus arteriosus or a constricting PDA in a patient with Berry syndrome may predict a poor prognosis. Thus, many patients receive prostaglandin E2 to maintain an open ductus arteriosus until further treatment [8,47,51,53]. On review, more than half of patients diagnosed within 3 months present with a large PDA, while patients diagnosed after 3 months all present with a large PDA.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the reconstructed aorta and the PA can both keep growing. However, as seen in our center together with the long-term follow-up in other literature ( 10 ), post-operative RPA stenosis is still the most common complication, owing to the difficulty in reconstruction and the compression due to a limited space next to the AAO. Bi et al ( 1 ) found that many patients (58.6%, 17/29) suffered from post-operative RPA stenosis, and seven patients (41%, 7/17) underwent reinterventions, including five patients were performed surgical repair and three patients were performed balloon angioplasty.…”
Section: Discussionmentioning
confidence: 55%
“…Hemodynamically, the intra-aortic patch was pushed toward the PA owing to the pressure gradient between AAO and PA, which might cause RPA stenosis or even LPA stenosis and the potential problem of the left ventricular outflow tract. Binsalamah et al ( 10 ) reported a case with type A of IAA and type III of APW showing a mild post-operative RPA stenosis by the technique similar to Park et al ( 15 ). Ando et al ( 9 ) also reported a similar case like Binsalamah but underwent two-stage surgical repair, and manifested that the maximal flow velocity of the aorta was 1.1 m/s and both RPA and LPA were 2.0 m/s.…”
Section: Discussionmentioning
confidence: 88%
“…The anomalous origin of the RPA is often combined with aortopulmonary window (AP window), aortic arch dissection [6,7], pulmonary aneurysm, pulmonary hypertension or heart failure [8]. In this study, for case with RPA originating from the ascending aorta, one case was combined with coarctation of the aorta, another one combined with VSD, tricuspid atresia, pulmonary valve atresia, visceral inversion and right isomerism, and the rest were not found to have been combined with other malformations.…”
Section: Anomalous Origin Of Unilateral Pulmonary Arterymentioning
confidence: 79%